Advances in the syntax of DP's : structure, agreement, and case - Bondaruk, Anna; Dalmi, Gréte; Grosu, Alexander; Trugman, Helen, (1962-2012) (Linguistik Aktuell/Linguistics Today ;, 2014)
This chapter argues for the view that Standard Free Relatives and Transparent Free Relatives have exactly the same bi-dimensional configurational structures, and against the view that they have distinct multi-dimensional structures, the transparent variety being externally headed by a token of a CP-internal post-copular phrase. It is argued that the proposed view yields superior analyses of the following facts: [i] Transparent Free Relatives are typically construed as existentially quantified, regardless of the quantificational force of the pivot, and [ii] certain case mismatch effects, predic.